The Role of Personalization and Online Store Trust on Purchase Intention Mediated by Customer Satisfaction - Lusy Endang Sri.D; Dassucik Dassucik; Sri Ayudha Mujianti (Information Technology and Science (ITScience), 2025)
This study explores the relationships between personalization, trust, customer satisfaction, and online purchase intention in e-commerce. As online shopping continues to grow, understanding the factors that drive consumer behavior becomes increasingly important for businesses seeking to improve their digital marketing strategies. The objective of this research is to examine how personalization and trust influence customer satisfaction and purchase intention, with a focus on the mediating role of customer satisfaction. Using Structural Equation Modeling (SEM), the study analyzes data from 173 buyers of a furniture retailer, CV Melindo Jember. The results reveal that both personalization and trust positively influence customer satisfaction, which, in turn, significantly impacts online purchase intention. Personalization was found to enhance customer satisfaction, and trust played a critical role in shaping both satisfaction and purchase intention. The study further demonstrates that customer satisfaction mediates the relationship between personalization, trust, and purchase intention. These findings have practical implications for e-commerce businesses, highlighting the importance of personalization strategies and trust-building measures in improving customer experiences and boosting sales. The research contributes to the understanding of consumer behavior in online shopping, providing actionable insights for businesses to increase purchase intention. However, further research is needed to explore these relationships in other industries and geographical regions, as well as to consider other potential mediators or moderators of the consumer decision-making process.